2002
DOI: 10.1021/ic020121v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Uranyl Compounds with Iminodiacetate and Oxydiacetate Displaying Variable Denticity

Abstract: Eight uranyl compounds containing the dicarboxylate ligands iminodiacetate (IDA) or oxydiacetate (ODA) have been characterized in the solid state. The published polymeric structures for [UO(2)(C(4)H(6)NO(4))(2)] and [UO(2)(C(4)H(4)O(5))](n) have been confirmed, while Ba[UO(2)(C(4)H(5)NO(4))(2)] x 3H(2)O, [(CH(3))(2)NH(CH(2))(2)NH(CH(3))(2)][UO(2)(C(4)H(4)O(5))(2)] [orthorhombic space group Pnma, a = 10.996(5) A, b = 21.42(1) A, c = 8.700(3) A, Z = 4], and [C(2)H(5)NH(2)(CH(2))(2)NH(2)C(2)H(5)][UO(2)(C(4)H(4)O(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 22 publications
7
64
0
Order By: Relevance
“…Moreover, titrations conducted with competing ligands allowed us to control the metal speciation and to avoid precipitation of hydroxo uranyl species. Iminodiacetic acid (IDA) was chosen as a competing ligand as it shows a quite simple speciation with uranyl and reliable equilibrium constants are reported . The conditional stability constants of the uranyl complexes formed with IDA were calculated and inserted in the fitting procedure according to models described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, titrations conducted with competing ligands allowed us to control the metal speciation and to avoid precipitation of hydroxo uranyl species. Iminodiacetic acid (IDA) was chosen as a competing ligand as it shows a quite simple speciation with uranyl and reliable equilibrium constants are reported . The conditional stability constants of the uranyl complexes formed with IDA were calculated and inserted in the fitting procedure according to models described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…The conditional stability constants of uranyl with the competing agent (IDA) were taken into account in the procedure. These constants were calculated at pH 7.4 from published global constants: trueUO22++IDA2-UO2IDA;4ptlogβ11pH0.166667em7.4=7.8 trueUO22++24ptIDA2-UO2(IDA)22-;4ptlogβ12pH0.166667em7.4=12.2 true24ptUO22++24ptIDA2-+24ptOH-(UO2)2(IDA)2(OH)22-;logβ22pH0.166667em7.4=21.4 …”
Section: Methodsmentioning
confidence: 99%
“…Thermodynamic [6] and structural [4,6] data on the complexation of U(VI) with ODA have revealed that the ether-oxygen of ODA could be in a bonding mode (R U-O ~ 2.5 -2.6 Å), non-bonding mode (R U-O ~ 3.12 Å), or dynamic mode between bidentate and tridentate configurations (R U-O ~ 2.90 Å) in solution. Whether the ether-oxygen participates in bonding with metal ions, particularly the dioxo-actinyl ions where steric hindrance may exist, has always been an interesting subject of study.…”
Section: Coordination Modesmentioning
confidence: 99%
“…Whether the ether-oxygen participates in bonding with metal ions, particularly the dioxo-actinyl ions where steric hindrance may exist, has always been an interesting subject of study. The M-O distances in these complexes are compared with those in a tridentate UO 2 (ODA) 2 2complex [4] in Figure 6. For the complexes of actinyl ions with DMOGA or TMOGA, we haven't identified the structures in solution.…”
Section: Coordination Modesmentioning
confidence: 99%
See 1 more Smart Citation